Application of Total Quality Management on Operational Performance - Rini, Poppy Laksita; Fikri, Muhammad Ali; Al Hanifah, Rossa (International Journal of Entrepreneurship and Business Management, 2024)
Purpose – The purpose of this study is to find out how customer satisfaction, employee empowerment, continuous quality improvement, and fact-based management are elements of TQM that can affect operational performance. Methodology/approach – This study is conducted in Quantitative Method by gathering primary data from employee of Bank Mandiri in the Special Region of Yogyakarta (DIY). The sampling technique is purposive sampling. The data that has been obtained is processed using the Smart PLS statistical tool. Findings – It was found that customer satisfaction, employee empowerment, and continuous quality improvement were proven to have a negative influence on operational performance. While fact-based management in this study is proven to have a positive influence on operational performance. Novelty/value – This study contributes to deliver knowledge about how the components of total quality management represented by customer satisfaction, employee empowerment, continuous quality improvement, and fact-based management affect operational performance of Banking Company, specifically Bank Mandiri in the Special Region of Yogyakarta (DIY) which has never been studied before.